English Songs As Media to Improve Vocabulary Mastery: A Case Study of One of Junior High Schools in Indonesia - Ulfah Nur Afifah; Yuyus Saputra; Nita Sari Narulita Dewi (Journal of Innovative and Creativity, 2025)
The purpose of this study was to improve students' mastery of English vocabulary using English songs. Conducted with two participants at a junior high school in Tasikmalaya City, West Java, Indonesia, the research utilized an interview technique to gather insights on students' experiences. The data obtained from the interviews were analyzed thematically, revealing several key findings. Firstly, students reported that they effectively remember new vocabulary through English songs, which aids in retention and recall. Secondly, the study indicated that vocabulary acquisition is significantly enhanced when students engage with English songs. Additionally, participants noted improvements in their pronunciation skills, allowing them to articulate words they previously found challenging. The research also highlighted that students could correct their spelling through exposure to song lyrics, reinforcing their learning experience. Moreover, students demonstrated initiative by seeking to understand the meanings of the words within the songs, further deepening their vocabulary mastery. Overall, the findings suggest that students tend to have positive perceptions of learning English through songs, as this method not only makes the learning process enjoyable but also effectively supports their language development. By integrating music into language education, teachers can foster a more engaging and productive learning environment for their students..